2012
DOI: 10.1016/j.neuron.2011.12.037
|View full text |Cite
|
Sign up to set email alerts
|

CYSL-1 Interacts with the O2-Sensing Hydroxylase EGL-9 to Promote H2S-Modulated Hypoxia-Induced Behavioral Plasticity in C. elegans

Abstract: SUMMARY The C. elegans HIF-1 proline hydroxylase EGL-9 functions as an O2-sensor in an evolutionarily conserved pathway for adaptation to hypoxia. H2S accumulates during hypoxia and promotes HIF-1 activity, but how H2S signals are perceived and transmitted to modulate HIF-1 and animal behavior is unknown. We report that the experience of hypoxia modifies a C. elegans locomotive behavioral response to O2 through the EGL-9 pathway. From genetic screens to identify novel regulators of EGL-9-mediated behavioral pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
159
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(171 citation statements)
references
References 62 publications
12
159
0
Order By: Relevance
“…The beneficial effects of H 2 S in treating ischemia/reperfusion injury and in pre-and postconditioning have been well documented, and it has been suggested that the beneficial effects of exogenous H 2 S are due to mimicking transient hypoxia, which is also used in conditioning (128). It is also evident that H 2 S is involved in long-term O 2 sensing through its inhibitory effects on hypoxia inducible factor (HIF)-1a expression (70,148,149,188), although opposite effects have also been reported (17,91,93). In an elegant study, Ma et al (93) identified a novel genetic pathway where an increase in H 2 S produced by prolonged (24 h) hypoxia increases HIF-1 expression in C. elegans.…”
Section: General Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…The beneficial effects of H 2 S in treating ischemia/reperfusion injury and in pre-and postconditioning have been well documented, and it has been suggested that the beneficial effects of exogenous H 2 S are due to mimicking transient hypoxia, which is also used in conditioning (128). It is also evident that H 2 S is involved in long-term O 2 sensing through its inhibitory effects on hypoxia inducible factor (HIF)-1a expression (70,148,149,188), although opposite effects have also been reported (17,91,93). In an elegant study, Ma et al (93) identified a novel genetic pathway where an increase in H 2 S produced by prolonged (24 h) hypoxia increases HIF-1 expression in C. elegans.…”
Section: General Metabolismmentioning
confidence: 99%
“…It is also evident that H 2 S is involved in long-term O 2 sensing through its inhibitory effects on hypoxia inducible factor (HIF)-1a expression (70,148,149,188), although opposite effects have also been reported (17,91,93). In an elegant study, Ma et al (93) identified a novel genetic pathway where an increase in H 2 S produced by prolonged (24 h) hypoxia increases HIF-1 expression in C. elegans. They showed that H 2 S promotes the interaction of CYSL-1 with EGL-9, thereby removing the inhibitory effect of EGL-9 on HIF-1.…”
Section: General Metabolismmentioning
confidence: 99%
“…The O2-ON response of young adult fat-2(wa17) (n>50 for each treatment) was continuously measured using a multi-worm tracker with a gasflow chamber system and quantified by customized MatLab algorithms as previously described [4]. For characterizing the locomotive behaviour of wild-type and fat-3(wa22), we determined the worm's speed and body bend frequency according to Hart, 2006 [30].…”
Section: Locomotive Behaviourmentioning
confidence: 99%
“…The nematode C. elegans can survive at a wide range of oxygen concentrations, but exhibits an aerotaxis behaviour prompting the worms to migrate to their preferred oxygen concentration of about 10 % [2]. Upon anoxia/reoxygenation, C. elegans shows the so-called "O2-ON" behavioural response that is characterised by a rapidly increased locomotion speed [3,4]. Recent studies suggest that evolutionarily conserved pathways contribute to ischemiareperfusion injury in mammalian cells and to the O2-ON response in C. elegans [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation